2017
DOI: 10.18203/2349-3291.ijcp20172515
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of asymptomatic hypoglycemia in term newborn babies weighing more than two kilograms

Abstract: Background: Neonatal hypoglycemia is a common metabolic problem especially in cases like prematurity, sepsis and small gestational age. Episodes of asymptomatic hypoglycemia may occur due to many risk factors. The present study aimed to evaluate the incidence of asymptomatic hypoglycemia in term new born babies weighing more than 2 kg, to study the plasma sugar level at various time points during first 48 hours of life and to study the effect of maternal factors like parity, mode of delivery, glucose infusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…In our study, males were more than females and similar results were found in Kumar et al, 4 Thirumalaikumarasamy S et al 17…”
Section: Discussionsupporting
confidence: 91%
“…In our study, males were more than females and similar results were found in Kumar et al, 4 Thirumalaikumarasamy S et al 17…”
Section: Discussionsupporting
confidence: 91%
“….75% were born by LSCS and 56.25% were born by vaginal delivery 15. Maturity: In present study, majority of newborns were preterm 169 (45.06%), 134 (35.73%) were term and 72 (19.21%) were post term.…”
mentioning
confidence: 49%
“…13 Babu et al showed that 5% mothers had Diabetes mellitus, 10% had HTN, 32.5% had PIH. [14][15][16]…”
Section: Co Morbid Mothersmentioning
confidence: 99%
“…Resolution of symptoms should occur with an increase in plasma glucose level [2]. Asymptomatic hypoglycemia may be seen in patients with type 1 diabetes mellitus and neonates [3,4]. Based on blood glucose levels, hypoglycemia may be classified into mild (level 1, blood glucose 55-70 mg/dL), moderate (level 2, blood glucose <54 mg/dL), or severe (level 3, blood glucose <40 mg/dL) [5].…”
Section: Introductionmentioning
confidence: 99%